KONSEP KEBAHAGIAN MARTIN SELIGMAN: SEBUAH PENELITIAN AWAL - Jusmiati Usman (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2017)
Happiness is a human nature. Every human being with all his desirable status and work is a feeling of happiness and tranquility. However, the facts in everyday life, not all humans that reach kebahagian intrinsic. Precisely many people are misguided in seeking happiness itself. In this article, researchers elaborate the concept of happiness Martin Seligman as a positive psychological figure that offers a unique concept of happiness. According to him, that humans can basically achieve authentic happiness with constant commitment in doing good in life. This concept is very interesting when associated with the concept of happiness in positive tasawuf